Integration of Artificial Intelligence (AI) in Human Resource Performance Assessment Systems to Support Good University Governance in Higher Education Institutions - Jauzaa Marva Ondrea Sugiyarto; Shinta Ratnawati; Azzahra Putri Harinda (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2026)
Higher education institutions face complex challenges in managing and evaluating human resource (HR) performance objectively, accountably, and sustainably. The urgency of developing technology-based assessment systems is increasing, especially in supporting the implementation of good university governance. This study aims to analyze the integration of Artificial Intelligence (AI) in HR performance evaluation systems in higher education institutions. The study employs a descriptive qualitative approach using a systematic literature review of relevant national and international scientific sources. The findings indicate that the use of AI in HR performance evaluation can enhance transparency, efficiency, and accuracy of evaluations while reducing subjective bias in decision-making. Several AI models employed include machine learning for performance prediction, natural language processing for qualitative data analysis, and algorithm-based decision support systems. AI integration also enables real-time performance monitoring and personalized HR development. The implications of these findings suggest that the adoption of AI in HR performance management supports the principles of good governance, such as accountability, participation, and effectiveness in university governance.